Evaluasi Perilaku Pekerja dengan Pajanan Panas dari Hasil Pelatihan Berbasis Kompetensi Berdasarkan Model Kirkpatrick di Divisi Pengolahan PT. XYZ - Yuliasari, Fanny Sarah; Hidayah, Nurul (Jurnal Kesehatan Komunitas, 2026)
Competency-Based Training (CBT) is a strategic approach in the mining industry to enhance both technical and non-technical skills of workers, particularly in high-risk activities such as Hot Work Permit (HWP) [2]. This study aims to evaluate behavioral changes among employees in the Processing Division of PT XYZ after participating in CBT programs. The research used a quantitative-qualitative approach with a cross-sectional case study design, involving 199 staff and non-staff employees who had completed HWP training. Data were collected through questionnaires, interviews, and direct observation, and analyzed using proportion tests, correlation tests, and logistic regression. The findings revealed positive perceptions from employees regarding the influence of training on HWP implementation, supported by supervisory aspects, compliance with Standard Operating Procedures (SOP), and personal factors. Significant positive effects were found from supervisory aspects on the implementation of hot work permits, as well as from training and personal factors on the use of Personal Protective Equipment (PPE). Nevertheless, external factors such as supervisory support and understanding of SOP compliance played a major role in sustaining behavioral changes. These findings confirm that CBT is effective in improving safe work behavior when supported by training, supervision, SOP compliance, and positive personal factors. The study concludes that Level 3 evaluation is essential as a foundation for improving training programs and strengthening workplace safety culture.